Anxiety and depression: a study of psychoaffective, family-related, and daily-life factors in celiac individuals - Nirla Gomes Guedes; Leonardo Alexandrino da Silva; Cristina Costa Bessa; Jorgiana Cavalcanti dos Santos; Viviane Martins da Silva; Marcos Venícios de Oliveira Lopes (Associação Brasileira de Enfermagem, 2020)
ABSTRACT Objective: To identify the prevalence of anxiety and depression and its association with psychoaffective, family-related, and daily-life variables of celiac individuals. Methods: Crosssectional study, developed with 83 celiac patients in Fortaleza. An instrument was applied with variables grouped in the categories: psychoaffective, family-related, and daily-life. Results: It was found that 52 celiac patients (62.7%) had anxiety and 29 (34.9%) had depression. The clinical conditions found and the number of symptoms increased the chance of anxiety/depression. The predominant factors in those with anxiety were Lack of control of the celiac disease (98.1%), Perceived clinical condition (75.0%), Daily obstacles for maintaining a gluten-free diet (63.4%), and Daily activities (55.8%). In those with depression, there was a higher prevalence of Lack of control of the celiac disease (100.0%), Perceived clinical condition (82.2%), and Daily obstacles for maintaining a gluten-free diet (69.0%). Conclusion: Celiac individuals with anxiety and depression frameworks presented a higher frequency of Perceived clinical condition, Insufficient social support (psychoaffective factors) and Daily obstacles for maintaining a gluten-free diet (daily-life factor).